Pelatihan Komputer untuk Santri Pemula sebagai Strategi Mengurangi Buta Aksara Digital di Dayah Darut Thalibin - Helmiah; Teuku Muana Refi (BA: Jurnal Pengabdian kepada Masyarakat, 2025)
The advancement of digital technology requires every individual to have basic computer literacy, including santri (students) in traditional pesantren environments. However, the reality on the ground shows that about 85% of beginner santri at Dayah Darut Thalibin still experience digital illiteracy due to limited access and minimal information technology training. This community service activity aims to reduce this gap through basic computer training. The method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The training was conducted over four weeks in eight sessions, covering hardware introduction, operating system operation, and the use of Microsoft Word and Excel. The results showed significant improvement: 92% of participants could recognize basic hardware functions, 86% were able to create simple documents using Word, and 70% mastered the basics of Excel. In addition to skill enhancement, 80% of participants demonstrated a positive attitude shift towards technology, including increased self-confidence and motivation for further learning.This program also encourages the dayah administration to incorporate digital literacy into their educational agenda. Thus, basic computer training has proven to be an effective and sustainable strategy in developing a generation of santri who are digitally literate and adaptive to the evolving times.